An event-triggered quantization communication strategy for distributed optimal resource allocation - Cai, Xin; Zhong, Huiru; Li, Yanbiao; Liao, Junbo; Chen, Xingzhi; Nan, Xinyuan; Gao, Bingpeng (Systems & control letters, 2023)
Taken limited communication resources in practical applications into consideration, this paper studies the distributed resource allocation problem for continuous-time multi-agent systems on switching networks. Transmission information among agents is quantized by a dynamic encoding/decoding scheme to reduce the amount of data transmitted in communication networks. Furthermore, an event-triggered communication scheme is designed to determine when to transmit quantized information to neighboring agents. Compared with the existing distributed event-triggered resource allocation algorithms, the proposed algorithm can reduce not only the communication frequency but also the amount of transmission data. Under mild conditions, all agents’ decisions asymptotically reach to the optimal allocation. It is analyzed that the proposed event-triggered quantization communication scheme is free of the Zeno behavior. A numerical example is given to verify the effectiveness of the proposed algorithm.